The Influence of Word of Mouth and Brand Image on Using Decisions Grabfood Services - Fikri Nazih Juniansyah; Karona Cahya Susena; Nia Indriasari (Journal of Indonesian Management, 2021)
The purpose of this study was to determine whether there is an influence of word of mouth and brand image on the decision to use Grab Food services in Bengkulu City. This research uses quantitative research methods, where research data contains numbers and is analyzed using statistics. With a sample of 100 respondents, respondents were given several statements about the influence of word of mouth and brand image on the decision to use Grabfood services. Simultaneous Hypothesis testing, Fratio value is 75,537 with probability value (sig.) = 0.000. meaning that the significance value is less than the probability value of 0.05 or the value (sig.) 0.000 < 0.05, then Ha is accepted. This means that the variable Word of Mouth (X1) , Brand image (X2) both have a positive and significant effect on the Decision to Use Grab Food Services in Bengkulu City.